Education on Hospitalization Reactions to Increase Parental Involvement in Yarsi General Hospital, Pontianak - Sari, Lintang; Kirana, Wahyu; Safitri, Dewin; Florensa, Florensa; Yousriatin, Fajar (Jurnal Keperawatan Profesional (KEPO), 2025)
Hospitalization not only causes anxiety and stress for children but also their parents. One of the factors behind this is the lack of parental knowledge about the disease and reactions to hospitalization, thus increasing anxiety which has an impact on the lack of parental participation in care. Parents with high anxiety levels tend to be less than optimal in caring for children while in the hospital, which can be shown by parental participation. This study aimed to analyze the effect of education on hospitalization reactions on parental participation in the children's room of Yarsi Pontianak General Hospital. The research design used was a quasi experiment with a pretest-posttest without control group approach. The sample size was 30 children who were treated in the pediatric room of Yarsi Pontianak General Hospital. The instrument used was a parent participation questionnaire that had been tested for validity and reliability. The bivariate test used Wilcoxon Signed Rank to identify the effect of education on hospitalization reactions on parental participation. The results of bivariate analysis using the Wilcoxon test obtained a p-value of 0,042 which indicated the effect of education on hospitalization reactions on parental participation. There is an effect of education about hospitalization reactions on parental participation in the children's room of Yarsi General Hospital Pontianak. Nurses are expected to be more active in involving parents in child care.